Shvedova Z. V. Phraseological conceptualization of good mental abilities of a person - Shvedova Z. V. (Philological Treatises, 2020)
Basing on the material, provided by Belarusian phraseological units with the meaning of good mental abilities, the article singles out the main metaphorical patterns for their formation and the ways of conceptualization of this abstract notion.